Validation of the Persian version of the summary of diabetes self-care activities scale (SDSCA) in pregnant women with gestational diabetes mellitus using a COSMIN methodology - Mahsa Maghalian; Mohammad Asghari Jafarabadi; Fatemeh Abbasalizadeh; Sakineh Mohammad-Alizadeh-Charandabi; Solmaz Ghanbari-Homaie; Mojgan Mirghafourvand (BMC Endocrine Disorders)
Abstract Background Gestational diabetes mellitus (GDM) is a condition with significant prenatal and postnatal implications. This study aimed to validate the Summary of Diabetes Self-Care Activities (SDSCA) measure in Iranian women with GDM, focusing on its psychometric properties. Methods The Persian version of the SDSCA was evaluated in 180 Iranian women with GDM. Following COSMIN guidelines, the instrument was translated into Persian, and its psychometric properties were assessed, including content validity, face validity, construct validity, internal consistency, test-retest reliability, measurement error, responsiveness, and interpretability. Floor and ceiling effects were also examined. Results The validity assessments showed strong content validity, with a Content Validity Index (CVI) of 0.93 and a Content Validity Ratio (CVR) of 0.97. Face validity yielded an impact score of 4.38. Exploratory factor analysis (EFA) identified three factors—diet, exercise, and blood sugar testing—accounting for 57.4% of the variance. Confirmatory factor analysis (CFA) confirmed the model’s excellent fit (CFI = 1.00, TLI = 0.99, NFI = 0.98, RFI = 0.96). The reliability analysis showed a Cronbach’s alpha of 0.78 and a McDonald’s omega of 0.91, with an intraclass correlation coefficient (ICC) of 0.92 (95% CI: 0.83–0.96). Ceiling effects were observed for blood sugar testing (26.7%), while floor effects were noted for exercise (6.7%) and blood sugar testing (6.1%). The Minimal Important Change (MIC) of 2.68 units exceeded the Smallest Detectable Change (SDC) of 1.11 units, indicating the tool’s ability to detect clinically meaningful changes. Conclusions The Persian version of the SDSCA demonstrates strong psychometric properties, including both reliability and validity, making it a suitable tool for assessing self-care behaviors in Iranian women with GDM. Its use in future research can enhance understanding of self-management in this population.